Influence of Residential Spatial Position to Trip Generation in Surabaya - Wahju Herijanto; Indrasurya B. Mochtar; Achmad Wicaksono (IPTEK Journal of Proceedings Series, 2017)
Zonal trip generation is usually assummed to be influenced only by demographic and economic variables. It is seldom to consider spatial position of the zones as an influence variables to its trip generation. In actual condition, people will consider strategic position of residential area when they choose to buy or rent of their home, in accordance with their place of activities such as working, studying for their children and shopping. This research aim is to calculate the influence of spatial position of residential zones from the activities centers to zonal trip generation in Surabaya, Indonesia. Surabaya has several activities centers that can be classified as urban centers and suburban centers. In order to define position of residential zones in relation with activities centers, travel time is defined as a spatial measure which can be measured using Google Maps. Trip generation data is compiled from origin-destination matrix from household interview survey. Regression analysis is used for calculation of the influence of spatial position of residential zones in relation to the activities centres to zonal trip generation. The result shows that travel time to urban center influences reduction of the residential trip generation more than travel time to suburban centers does. However, still many trips were not influenced by travel time from residential to city center since housing ownership in Surabaya is fixed system more than flexible one, and housing at periphery area much cheaper than at city center.